Knowledge of general dentists, endodontists and pediatric dentists about the management on dental traumas: a survey in turkey - Yusufoğlu, Selen İnce and Tulumbacı, Fatih (Brazilian Dental Science, 2020)
Objective: The purpose of this study was to determine endodontists, pedodontists and general dentists’ knowledge of management of dental trauma. Material and methods: A web-based survey including 13 questions was prepared using Google forms, and a link to the survey was sent to the general dentists, endodontists and paediatric dentists via social media. The questionnaire asked for information regarding the age, gender, state of education, type of institution and knowledge levels about dental traumas. A total of 258 questionnaires were returned, and the One-Way Anova for practitioners’ knowledge and the statistical analysis of the relationship between gender, vocational training and training by using Mann-Whitney U tests for participants. Results: As a result of statistical analysis, although there was no statistical difference between pedodontists and endodontists in their knowledge levels, it was found that both occupational groups had higher knowledge level than general dentists (p = 0,0001). While there was a significant difference between practitioners at university and oral and dental health hospital (p = 0.0001), there was no difference between practitioners in university hospital and private office (p = 0.065). Conclusions: In conclusion, general dentists had knowledge of inadequate dental trauma management and the knowledge level of dentists working at oral and dental hospital was lower. Keywords Dental Trauma; Knowledge Level; General Dentist; Endodontists; Pediatric Dentistry.